Pluripotent stem cell‐derived radial glia‐like cells as stable intermediate for efficient generation of human oligodendrocytes. Issue 12 (30th June 2015) - Gorris, Raphaela; Fischer, Julia; Erwes, Kim Lina; Kesavan, Jaideep; Peterson, Daniel A.; Alexander, Michael; Nöthen, Markus M.; Peitz, Michael; Quandel, Tamara; Karus, Michael; Brüstle, Oliver
<x xml:space="preserve">Abstract</x> Neural precursor cells (NPCs) derived from human pluripotent stem cells (hPSCs) represent an attractive tool for the in vitro generation of various neural cell types. However, the developmentally early NPCs emerging during hPSC differentiation typically show a strong propensity for neuronal differentiation, with more limited potential for generating astrocytes and, in particular, for generating oligodendrocytes. This phenomenon corresponds well to the consecutive and protracted generation of neurons and GLIA during normal human development. To obtain a more gliogenic NPC type, we combined growth factor‐mediated expansion with pre‐exposure to the differentiation‐inducing agent retinoic acid and subsequent immunoisolation of CD133‐positive cells. This protocol yields an adherent and self‐renewing population of hindbrain/spinal cord radial glia (RG)‐like neural precursor cells (RGL‐NPCs) expressing typical neural stem cell markers such as nestin, ASCL1, SOX2, and PAX6 as well as RG markers BLBP, GLAST, vimentin, and GFAP. While RGL‐NPCs maintain the ability for tripotential differentiation into neurons, astrocytes, and oligodendrocytes, they exhibit greatly enhanced propensity for oligodendrocyte generation. Under defined differentiation conditions promoting the expression of the major oligodendrocyte fate‐determinants OLIG1/2, NKX6.2, NKX2.2, and SOX10, RGL‐NPCs efficiently convert into NG2‐positive oligodendroglial progenitor cells (OPCs) and are subsequently capable of in vivo myelination. Representing a stable intermediate between PSCs and OPCs, RGL‐NPCs expedite the generation of PSC‐derived oligodendrocytes with O4‐, 4860‐, and myelin basic protein (MBP)‐positive cells that already appear within 7 weeks following growth factor withdrawal‐induced differentiation. Thus, RGL‐NPCs may serve as robust tool for time‐efficient generation of human oligodendrocytes from embryonic and induced pluripotent stem cells. GLIA 2015;63:2152–2167